Human bone marrow mesenchymal stem cells for retinal vascular injury - Wang, Jin-Da; Jonas, Jost B. (Acta ophthalmologica, 2017)
Purpose: To examine the potential of intravitreally implanted human bone marrow-derived mesenchymal stem cells (BMSCs) to affect vascular repair and the blood-retina barrier in mice and rats with oxygen-induced retinopathy, diabetic retinopathy or retinal ischaemia-reperfusion damage. Methods: Three study groups (oxygen-induced retinopathy group: 18 C57BL/6J mice; diabetic retinopathy group: 15 rats; retinal ischaemia-reperfusion model: 18 rats) received BMSCs injected intravitreally. Control groups (oxygen-induced retinopathy group: 12 C57BL/6J mice; diabetic retinopathy group: 15 rats; retinal ischaemia-reperfusion model: 18 rats) received an intravitreal injection of phosphate-buffered saline. We applied immunohistological techniques to measure retinal vascularization, spectroscopic measurements of intraretinally extravasated fluorescein-conjugated dextran to quantify the blood-retina barrier breakdown, and histomorphometry to assess retinal thickness and retinal ganglion cell count. Results: In the oxygen-induced retinopathy model, the study group with intravitreally injected BMSCs as compared with the control group showed a significantly (p = 0.001) smaller area of retinal neovascularization. In the diabetic retinopathy model, study group and control group did not differ significantly in the amount of intraretinally extravasated dextran. In the retinal ischaemia-reperfusion model, on the 7th day after retina injury, the retina was significantly thicker in the study group than in the control group (p = 0.02), with no significant difference in the retinal ganglion cell count (p = 0.36). Conclusions: Intravitreally implanted human BMSCs were associated with a reduced retinal neovascularization in the oxygen-induced retinopathy model and with a potentially cell preserving effect in the retinal ischaemia-reperfusion model. Intravitreal BMSCs may be of potential interest for the therapy of retinal vascular disorders.
First published: 03 November 2016
Gesehen am 08.10.2018